Microencapsulation of bull spermatozoa: Its viability in alginate-egg yolk media - DA, Kusumaningrum; B, Purwantara; TL, Yusuf; P, Situmorang (Indonesian Animal Sciences Society, 2015)
Microencapsulation of spermatozoa is a process to entrap a number of spermatozoa in microcapsule. Alginate, as a natural polymer polysaccharide is commonly used in cell microencapsulation. Tris Yolk Citrate buffer is a good buffer for spermatozoa dilution, therefore this experiment aimed to determine optimal concentration of alginate and egg yolk to sperm quality in bull spermatozoa microencapsulation. Concentration of egg yolk and alginate in media of encapsulation were determined in applications of sperm microencapsulation. Four bulls were used as semen source and only semen with good quality were used in this study. Poolled semen was diluted using the medium to get final concentration 100 x 106 cell/ ml. The first study was conducted to determine the effect of concentration of alginate (0, 1, and 1.5%) on viability of spermatozoa. The second study to determine the effect of alginate concentration, egg yolk and its interaction was done by comparing two levels of alginate (1 and 1.5%) with four levels of egg yolk (5, 10, 15 and 20%). Viability of spermatozoa, motility (M), live spermatozoa (L) and Intact Apical Ridge (IAR) were observed at 0, 1, 2 and 3 h incubation at room temperature. Results indicated that alginate concentration increased the osmolality and viscosity but did not affect pH of the medium. The osmolality and viscosity of medium were 275, 325, 425 and 1.12, 26.62, 47.98 for concentration of alginate 0, 1 and 1.5% respectively. Percentage of motility is significantly lower (P<0.05) in alginate medium than those of control, and 1.5% alginate could produce more uniform beads. Concentration of alginate, egg yolk and its interaction did not significantly affect viability of sperm. It is concluded that the combination of 1.5% alginate with 5, 10, 15 or 20% egg yolk can be used as media for sperm encapsulation. Key Words: Microencapsulation, Spermatozoa, Sodium Alginate, Egg Yolk, Viability